Inhibition of ATP-sensitive potassium channels by haloperidol. - Yang, S; Proks, P; Ashcroft, F; Rupnik, M (2004)
Chronic haloperidol treatment has been associated with an increased incidence of glucose intolerance and type-II diabetes mellitus. We studied the effects of haloperidol on native ATP-sensitive potassium (K(ATP)) channels in mouse pancreatic beta cells and on cloned Kir6.2/SUR1 channels expressed in HEK293 cells. The inhibitory effect of haloperidol on the K(ATP) channel was not mediated via the D2 receptor signaling pathway, as both D2 agonists and antagonists blocked the channel. K(ATP) currents were studied using the patch-clamp technique in whole-cell and outside-out patch configurations. Addition of haloperidol to the extracellular solution inhibited the K(ATP) conductance immediately, in a reversible and voltage-independent manner. Haloperidol did not block the channel when applied intracellularly in whole-cell recordings. Haloperidol blocked cloned Kir6.2/SUR1 and Kir6.2DeltaC36 K(ATP) channels expressed in HEK cells. This suggests that the drug interacts with the Kir6.2 subunit of the channel. The IC(50) for inhibition of the K(ATP) current by haloperidol was 1.6 microM in 2 mM extracellular K(+) concentration ([K(+)](o)) and increased to 23.9 microM in 150 mM [K(+)](o). The Hill coefficient was close to unity, suggesting that the binding of a single molecule of haloperidol is sufficient to close the channel. Haloperidol block of K(ATP) channels may contribute to the side effects of this drug when used therapeutically.